2004
DOI: 10.1177/107110070402500204
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment for Anterior Impingement Exostosis of the Ankle: Application of Three-Dimensional Computed Tomography

Abstract: The purpose of this study was to evaluate the operative results of excision of anterior impingement exostoses of the ankle. Preoperative three-dimensional computed tomography (3DCT) was used to make the diagnoses. The authors evaluated 16 ankles of 16 patients who underwent arthroscopic resection of the osteophytes of their anterior distal tibia or dorsal talus. They were followed up for 24-51 months. All 16 patients had 3DCT preoperatively, which allowed the authors to determine the exact location, shape, siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Data from this investigation showed that males were significantly more likely than females to have spurs capable of causing AAI. While no previous study in the literature has examined the prevalence of spurs in relation to gender, the greater prevalence in males is consistent with findings from smaller clinical studies reporting on patients with bony exostoses, where most subjects were male (Berberian et al, 2001;Moon et al, 2010;Scranton and McDermott, 1992;Takao et al, 2004;Tol and van Dijk, 2004;van Dijk et al, 1997van Dijk et al, , 2002. While the predominance in males could be related to greater male participation in activities requiring extreme range of motion of the ankle, resulting in repetitive microtrauma contributing to spur development (Massada, 1991), a number of studies have examined the high rate of bony exostoses in the female ballet dancing population (Nihal et al, 2005;O'Kane and Kadel, 2008;Stoller et al, 1984).…”
Section: Discussionsupporting
confidence: 82%
“…Data from this investigation showed that males were significantly more likely than females to have spurs capable of causing AAI. While no previous study in the literature has examined the prevalence of spurs in relation to gender, the greater prevalence in males is consistent with findings from smaller clinical studies reporting on patients with bony exostoses, where most subjects were male (Berberian et al, 2001;Moon et al, 2010;Scranton and McDermott, 1992;Takao et al, 2004;Tol and van Dijk, 2004;van Dijk et al, 1997van Dijk et al, , 2002. While the predominance in males could be related to greater male participation in activities requiring extreme range of motion of the ankle, resulting in repetitive microtrauma contributing to spur development (Massada, 1991), a number of studies have examined the high rate of bony exostoses in the female ballet dancing population (Nihal et al, 2005;O'Kane and Kadel, 2008;Stoller et al, 1984).…”
Section: Discussionsupporting
confidence: 82%
“…In addition to standard ankle radiographs, a forced dorsiflexion lateral radiograph of the ankle was useful for the diagnosis of bony impingement. Oblique radiographs 18 and three-dimensional CT 16 also may be useful to demonstrate bony impingement but were not required in these dancers. MRI also was not routinely used in this series and usually is not required for the diagnosis of impingement, 7 but it may be useful in the evaluation of other ankle derangements such as osteochondritis dissecans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the odds ratio of spurs was comparable to that of medial joint space narrowing, we believe that ankle spurs do not reflect joint space narrowing, which is the fundamental element of OA. We frequently see young patients with spurs or subchondral sclerosis with normal articular cartilage, and numerous studies have failed to find a relationship between spurs and OA in the ankle [12,36,37,49,51]. Our series included only patients older than 40 years; if we did not limit the age, the sensitivity of spurs for detecting OA would have been reduced.…”
Section: Discussionmentioning
confidence: 99%